2000
DOI: 10.1086/501749
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Transmission of Tuberculosis (TB) Associated With Care of an Infant With Peritoneal TB

Abstract: Nosocomial transmission of tuberculosis (TB) after exposure to infected peritoneal fluid has not been described. We report the exposure of 111 healthcare workers to infected dialysate from an infant with TB peritonitis. Two (5%) of 39 primary-care nurses, but no doctors or environmental service workers, had apparent tuberculin skin test conversions, raising the concern that patients with peritoneal TB may be a source for nosocomial transmission of TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Nosocomial transmission of M. tuberculosis in paediatric wards has been rarely described, since children aged <10 years with pulmonary TB are rarely contagious. Four previous studies have reported nosocomial transmission where the case age at initial diagnosis was <1 year [5][6][7][8] ; in one of these reports, TB transmission was attributed to an infectious adult visitor accompanying the infant [5]. In our experience, neither the infant's mother, who remained with her child during the whole hospital stay, nor other household members who visited the child during hospitalization, showed signs of active infection.…”
mentioning
confidence: 54%
“…Nosocomial transmission of M. tuberculosis in paediatric wards has been rarely described, since children aged <10 years with pulmonary TB are rarely contagious. Four previous studies have reported nosocomial transmission where the case age at initial diagnosis was <1 year [5][6][7][8] ; in one of these reports, TB transmission was attributed to an infectious adult visitor accompanying the infant [5]. In our experience, neither the infant's mother, who remained with her child during the whole hospital stay, nor other household members who visited the child during hospitalization, showed signs of active infection.…”
mentioning
confidence: 54%
“…Transmission has also been described in a patient with genital TB who had multiple irrigations and disseminated TB diagnosed at autopsy 4 and in an infant with TB peritonitis undergoing peritoneal dialysis. 5 These reports have brought into question appropriate infection control measures for cutaneous TB.…”
Section: Discussionmentioning
confidence: 99%
“…5 Frampton et al described an outbreak of TB that had a 19% rate of TST conversions among HCWs exposed to a patient with skin ulcers, who required multiple debridements. 6 Lastly, 5% of nurses exposed to an infant with peritoneal TB had a newly positive TST 10 Failure to identify and appropriately isolate patients with TB has substantial consequences. 11 This study delineates the extent of transmission among HCWs as a result of unrecognized genitourinary tract TB, the second most common site of extrapulmonary TB after lymphadenitis.…”
Section: Discussionmentioning
confidence: 99%